2021
DOI: 10.1186/s12864-021-08033-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of races 1, 2, 5 and 6 of Fusarium oxysporum f.sp. pisi in a susceptible pea host identifies differential pathogenicity profiles

Abstract: Background The fungal pathogen Fusarium oxysporum f.sp. pisi (Fop) causes Fusarium wilt in peas. There are four races globally: 1, 2, 5 and 6 and all of these races are present in Australia. Molecular infection mechanisms have been studied in a few other F. oxysporum formae speciales; however, there has been no transcriptomic Fop-pea pathosystem study. Results A transcriptomic study was carried out to understand the molecular pathogenicity differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…for MoCDIP4, which was first discovered in Magnaporthe oryzae ( Chen et al 2013 ) and since reported in F. oxysporum f. sp. pisi ( Achari et al 2021 )), but most had scattered distributions across the group ( supplementary fig. S6, Supplementary Material online), which may be the result of frequent horizontal gene transfer (e.g., van Dam and Rep 2017 ; Peck et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…for MoCDIP4, which was first discovered in Magnaporthe oryzae ( Chen et al 2013 ) and since reported in F. oxysporum f. sp. pisi ( Achari et al 2021 )), but most had scattered distributions across the group ( supplementary fig. S6, Supplementary Material online), which may be the result of frequent horizontal gene transfer (e.g., van Dam and Rep 2017 ; Peck et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modelling of the MoCDIP4 effector used as template the structure of lytic polysaccharide monooxygenase GH61D from Phanerochaete chrysosporium . MoCDIP4 is a cell death-inducing effector [ 53 ]. Pfam analysis indicates that it corresponds to auxiliary activity family 9, AA9 (formerly GH61) domain, and CATH indicates an enzyme accession EC1.14.99.54, which corresponds to lytic polysaccharide monooxygenase.…”
Section: Resultsmentioning
confidence: 99%
“…spp. ( van Dam et al, 2016 ; Czislowski et al, 2018 ; Achari et al, 2021 ; Batson et al, 2021 ), were investigated in this study to assess their presence in the four FOA isolates. The results unveiled a narrow set of these effectors, namely homologs of SIX1, SIX6, SIX9, SIX11, and SIX14, extending the repertoire of known SIX genes within the FOA species.…”
Section: Discussionmentioning
confidence: 99%